Human Caused Mortality in the Leopard (Panthera pardus) Population of Nepal - Thapa, Tej B. (Journal of Institute of Science and Technology, 2015)
Estimating cause specific leopard (Panthera pardus) mortality is critical to their conservation. This paper examined leopard death reports during 2006-2013 in order to estimate cause-specific mortality, identify conservation issues related to leopard mortality and provide recommendations for reducing human-caused mortality in Nepal. Data revealed that the leopards in the human dominated landscape are susceptible to variation in survival caused by human induced mortality (65%), with retaliation (31%) and lethal control (20%) of declared problem leopard as a significant part. Elevated human induced mortality can cause large scale stochasticity influencing population dynamics of leopard. The conservation of leopards needs to acknowledge strategies to limit retaliatory killings and lethal control in the plans, while addressing its conflicts with human. Efforts to reduce human-caused mortality should focus on reducing poaching and deaths from human-leopards conflicts. Journal of Institute of Science and Technology, 2014, 19(1): 155-159